Strategy for increasing production and conservation of wood from farm land for raising farmers income - BHARTI, V. K.; BHAN, SURAJ (Journal of Soil and Water Conservation, 2020)
We depend on forests for our survival, from the air we breathe to the wood we use and apart from large variety of benefits, forests is a prime source of livelihood for millions of the poor people. Besides providing habitats for animals and livelihoods for humans, forests also offer watershed protection, prevent soil erosion and mitigate climate change. Forests not only contribute to GDP but more importantly provide employment and livelihoods to millions of poor people, who are mainly dependent on forests. Besides, they are also the main source of meeting food, fuel, fodder and timber requirements of the forest dwellers. Wood is one of the important forest products of commercial value and is renewable in nature. Forests have been main source of timber and fuel wood before the present Forest Policy came into existence. Due to change in objectives of forest Policy, farm forestry and agroforestry have grown in importance over recent decades in India and provide the bulk of timber for the growing economy of our country. The supply of wood is not enough to meet the present demand of our country that is why we are more dependent on import of wood and allied products. In an effort to make a balance between the objectives of production and conservation, a portion of the existing degraded forest land can be made open for the private enterprises having real interests who are committed to convert them for productive use. The forest land may be put to use exclusively for conservation of biodiversity and generation of complementary intangible benefits. The Forest department, keen on conservation to protect the National interest and the private enterprises interested for increased and assured supply of forestry resources as their raw materials. Plantations on degraded forestland will also act as green boundaries around the standing well-stocked forests and help facilitate their protection from timber mafias.